Knowledge and Attitude towards Anaphylaxis Reaction by Local Anesthesia among Dental Practitioners - Shahida Maqbool, Syed Muhammad Abul Hasan Ali, Hafsa Niaz, Syed Muhammad Ali Akbar, Sobia Siddique, Sarah Shami, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anaphylaxis or Type I hypersensitivity response is an acute, severe, and potentially life-threatening response to an allergen. It occurs as an immune mediated reaction due to the release of mediators by mast cells. The anaphylactic response involves skin, cardiovascular, respiratory or gastrointestinal systems. In dental settings, anaphylaxis can be faced in reaction to multiple medications including the administration of local anesthetic agents. The reaction involves difficulty in breathing, light headedness, wheezing or clammy skin. The knowledge and attitude of the treating dentist related to the anaphylaxis reaction is of prime importance as it may result in morbidity or mortality if not managed properly. Aim and objective: The aim of the study was to assess the knowledge and attitude of dental practitioners in Islamabad-Rawalpindi related to anaphylaxis reactions in patients who have been administered local anesthesia. Method: This cross-sectional study was conducted in Islamabad-Rawalpindi between Jan to June 2021. Total 377 dentist were enrolled in this study after taking consent the closed-ended questionnaire-filled. The questionnaire had two sections regarding the knowledge and practice attitude towards anaphylaxis reaction in response to local anesthesia. The data was analyzed by chi-Square test using SPSS version 24. Results: There were 377 dentists in the sample, with the age between 5-30 years old, with less than 5 years of experience. Only 4% of dentists said they routinely offer a test dosage, despite the fact that 96% of dentists had the practice of asking about previous medication allergies before beginning treatment. Just 28.9% of dentists were doing aspiration before the administration of local anesthesia with 63.1% were checked expiry date. Interestingly, most dentists kept epinephrine, antihistamine, corticosteroids, glucagon, and albutamol as emergency medicine but 79.7% agreed on epinephrine as a drug of choice and injected intramuscularly. Conclusion: Although anaphylaxis during dental operations is uncommon, it may have serious repercussions if it does occur. Results from the current research highlight dentists' knowledge gaps when it comes to dealing with adverse responses. Keywords: Anaphylaxis, Epinephrine, Hypersensitivity, Local anesthetic agent